2018
DOI: 10.1186/s12957-018-1339-0
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of suboptimal cytoreductive surgery in patients with advanced ovarian cancer based on preoperative and intraoperative determination of the peritoneal carcinomatosis index

Abstract: BackgroundThe peritoneal carcinomatosis index (PCI) can be used to quantify the tumor burden in patients with advanced ovarian cancer. The aim of the present study was to establish a predictive model for suboptimal cytoreductive surgery (SCS) (residual tumor of > 1 cm) using preoperative and intraoperative determination of the PCI.MethodsIn total, 110 consecutive patients treated for advanced ovarian cancer during a 4-year period in our institution were assessed. Eighty of these patients were eligible for prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 25 publications
1
44
0
4
Order By: Relevance
“…Furthermore, we believe that patient outcome is particularly interesting to highlight and is likely more relevant than surgical findings as a standard of reference for imaging studies. Interestingly, CT-PCI can be used to preoperatively estimate the surgical challenges and postoperative complications in women with OC [8]. Also, Diaz et al have shown that peritoneal disease quantified by CT-PCI in advanced-stage ovarian cancer patients correlated with presurgical CA-125 levels and 5-year survival [9].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, we believe that patient outcome is particularly interesting to highlight and is likely more relevant than surgical findings as a standard of reference for imaging studies. Interestingly, CT-PCI can be used to preoperatively estimate the surgical challenges and postoperative complications in women with OC [8]. Also, Diaz et al have shown that peritoneal disease quantified by CT-PCI in advanced-stage ovarian cancer patients correlated with presurgical CA-125 levels and 5-year survival [9].…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with our results, showing increasing CT-PCI to be significantly related to impaired OC-survival, even after adjustment for histological subtype and clinical stage. Previous studies [8,9] have addressed stage III and IV OC. However, we believe that it is important to include all OC stages since, in daily clinical practice, at the time of imaging, the clinical stage is unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preoperative PCI restaging by both methods was performed by two radiologists independently including differences in statistical analysis to generate generalized values and compared with intraoperative evaluation. Patients were categorized by us according to the value of intraoperative PCI into three groups (PCI<10, 10<PCI<20, PCI>20), due to the complexity of achieving optimal cytoreduction in these cases of the prevalence of tumour process and the index of completeness of cytoreduction, which illustrated radicality intervention [8,9]. The research was carried out within the framework of the scientific work of the Department of Surgery No.…”
Section: Methodsmentioning
confidence: 99%
“…Another way to characterize the tumor burden is through visual quanti cation of the tumor in the peritoneal cavity (PCI), rst described by Sugarbaker in 1998 for colorectal cancer [15,38,44]. A high peritoneal cancer index (PCI) indicates a worse surgical outcome and suggests considering other treatment options for the patient than primary surgery [10,22]. PCI in AOC has not been used outside clinical of studies.…”
Section: Introductionmentioning
confidence: 99%